Emissions Characteristics and Engine Performance from the Interaction Effect of EGR and Diesel-Ethanol Blends in Diesel Engine - Mohammed Ali Fayad; Moafaq Kaseim Al-Ghezi; Sanaa A Hafad; Slafa I Ibrahim; Marwa K Abood; Hind A Al-Salihi; Louay A Mahdi; Miqdam Tariq Chaichan; Hayder Abed Dhahad (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Recently, most of the researchers focused on provide lower greenhouse gas emissions that emitted from diesel engines by using renewable fuels to be good alternative to the conventional diesel fuel. Ethanol can be derived from renewable sources such as sugar cane, corn, timber and dates. In the current study, the ethanol fuel used in the tests was derived from the dates. The effects of using exhaust gas recirculation (EGR) diesel-ethanol blend (E10) with on engine performance and emissions characteristics have been studied in diesel engine under various engine loads. This study focused the use of oxygen in the bio-ethanol composition to compensate for the decrease occurred by the addition of EGR, which improves the engine performance and reduces its emissions. In this experiment, the ratios of EGR were 10%, 20% and 30% as well as 10% ratio of ethanol was blended into the diesel fuel blend under fixed engine speed. A traditional (without additional systems to reduce emissions) four cylinders direct injection (DI) diesel engine was used for all tests. The brake specific fuel consumption (BSFC) increased with increasing the EGR ratio by 10%, 20% and 30% by 18.7%, 22.4% and 37.4%, respectively. The thermal efficiency decreased under variable conditions of engine load for different ethanol blends. Furthermore, the emissions of NOX decreased when fuelled B10 into the engine in comparison with diesel under low engine load. Significant reduction in the NOx emissions were found when applied EGR in the tests than to the absence EGR for E10 blend and diesel. The NOx reduction rate was 12.3%, 30.6% and 43.4% when EGR rate was 10%, 20% and 30%, respectively. In addition, the concentrations of HC and CO emissions decreased more by 8.23% and 6.4%, respectively, when using E10 in comparison with the diesel for various engine loads. It is indicated that the oxygen reduction by EGR effect was compensated from ethanol blend combustion. The results showed that the combination use of E10 and EGR leads to significant reduction in engine emissions accompanied with partial reduction in the engine performance.